Les sociologies de l’enfance face à la parole enfantine - Ghislain Leroy (Recherches en Éducation)
This article scans and articulates a number of sociological works that document the status of children’s speech in contemporary society. This text is also the occasion of an epistemological reflection on the “sociology of childhood”, or rather the “sociologies of childhood”. In studying how they conceptualize the child’s speech, this article raises the question of what opposes but also brings together the various currents that make up the field, in particular around the question of “determination” or “autonomy” of child speech. Different conceptions of socialization are often the origin of debates. Moderately, avenues of work and perspectives for dialogue are discussed.